Some Hermite-Hadamard Type Inequalities with the Aid of Newly Defined Double Post-Quantum Integrals (Journal of Nonlinear Modeling and Analysis, 2025)
In the present paper, we first give four post-quantum integrals forfunctions of two variables, denoted by $_{ac}T_{p,q},$ $^d_ aT_{p,q},$ $^b_cT_{p,q}$ and $^{bd}T_{p,q}.$ Afterwards, each of these newly defined integrals is illustrated. Moreover, some newHermite-Hadamard inequalities are established based on these definitions. Wealso show the correctness of these inequalities with the aid of some numericalexamples.